2005
DOI: 10.1051/apido:2005011
|View full text |Cite
|
Sign up to set email alerts
|

Drone competition at drone congregation areas in four Apis species

Abstract: -In Apis mellifera the estimated average number of drones visiting a drone congregation area (DCA) was 11 750 + 2 145. Drones of the species Apis cerana, A. koschevnikovi, A. dorsata and A. mellifera, which pursued a queen dummy moving in circular course, flew in a comet shaped formation. Median numbers of drones in a comet ranged from 9 drones (A. koschevnikovi) to 31 drones (A. mellifera).In none of the species we observed aggression between drones. Drone density behind the queen and distance to the queen se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 32 publications
(45 reference statements)
0
65
1
5
Order By: Relevance
“…Furthermore, such virulence estimates may well depend on which host fitness parameters are investigated and which tissues are studied. It has been shown that drones are under strong selection for flight performance and wing symmetry during mating flights (Koeniger et al 2005b;Jaffé and Moritz 2010). However, the endophallus has no direct influence on flight ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, such virulence estimates may well depend on which host fitness parameters are investigated and which tissues are studied. It has been shown that drones are under strong selection for flight performance and wing symmetry during mating flights (Koeniger et al 2005b;Jaffé and Moritz 2010). However, the endophallus has no direct influence on flight ability.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong selection for drone flight performance to DCAs (Koeniger et al 2005b;Jaffé and Moritz 2010), as well as for general health and vitality during the 10-day in-hive drone maturation period prior to mating flights. Indeed, most drones infested by mites during the pupal stage are expelled from the colony before reaching sexual maturity ).…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees (Apis spp.) are highly polyandrous (Koeniger et al, 2005), though stingless bees are generally monandrous (Paxton et al, 1999b;Peters et al, 1999). Arguments for and against polyandry in eusocial Hymenoptera have been discussed at length elsewhere (Palmer and Oldroyd, 2000;Crozier and Fjerdingstad, 2001;Strassmann, 2001;Brown and Schmid-Hempel, 2003).…”
Section: Female Monogamymentioning
confidence: 99%
“…Mating in the honey bee A. mellifera never occurs within the colony but at flyways or 'drone congregation areas' (Koeniger, 1991;Koeniger et al, 2005), a pattern of mating that has probably evolved as a means to reduce inbreeding (Page, 1980). The deleterious effects of consanguineous mating are profound for haplodiploid species like A. mellifera with complementary sex determination (CSD, Beye et al, 2003) because inbreeding leads to the production of diploid males that are usually considered sterile.…”
Section: Inbreedingmentioning
confidence: 99%
See 1 more Smart Citation